Effective European Antitrust : Does EC Merger Policy Generate Deterrence? - Joseph A. Clougherty; Tomaso Duso; Miyu Lee; Jo Seldeslachts (Economic Inquiry, 2016)
We estimate the deterrence effects of European Commission (EC) merger policy instruments over the 1990–2009 period. Our empirical results suggest phase-1 remedies uniquely generate robust deterrence as - unlike phase-1 withdrawals, phase-2 remedies, and preventions - phase-1 remedies lead to fewer merger notifications in subsequent years. Furthermore, the deterrence effects of phase-1 remedies work best in high-concentration industries, that is, industries where the Herfindahl Hirschman Index is above the 0.2 cut-off level employed by the EC. Additionally, we find phase-1 remedies do not deter clearly pro-competitive mergers, but do deter potentially anti-competitive mergers in high-concentration industries.
Keywords: 330